Difficulties in selecting antiarrhythmic therapy in a patient with left ventricular noncompaction and atrial septal defect: a case report - M. R. Skhirtladze; E. A. Losik; E. L. Bueverova; A. S. Cherenda (Кардиоваскулярная терапия и профилактика, 2024)
Introduction. Left ventricular noncompaction (LVNC) is a rare heterogeneous pathology characterized by a two-layered structure with a predominance of non-compact layer in the form of multiple trabeculations and pockets between them, communicating with the left ventricular cavity. One of the rare LVNC phenotypes is a combination with congenital heart defects, including atrial septal defect (ASD).Brief description. The article presents a case report describing the difficulties of selecting antiarrhythmic therapy in a patient with LVNC and ASD, complicated by arrhythmias due to heart failure. The diagnosis of LVNC was confirmed by the Petersen criterion using magnetic resonance imaging.Discussion. Cardiac arrhythmias in patients with LVNC and congenital heart defects, as a result of both anatomical and hemodynamic causes of electrical heart instability, constitute a danger of thromboembolism and sudden cardiac death, and also contribute to heart failure progression. The case is of interest due to the rare combination of LVNC and ASD, complicated by frequent episodes atrial fibrillation and premature ventricular contractions in the form of parasystoles, as well as difficulties in selecting antiarrhythmic therapy. Pulmonary vein cryoballoon ablation eliminated the source of atrial fibrillation. Ventricular ectopic activity was stopped using the anticonvulsant drug carbamazepine.